2005
DOI: 10.2741/1524
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-somatostatin interactions in regulating cancer cell growth

Abstract: Opioids and somatostatin mediate their cellular effects through specific membrane receptors. Three major receptor classes (delta, mu and kappa) were identified for opioids, while for somatostatin, five different receptor classes (SSTR1-5) have been cloned. Through the interaction with their receptors, opioids and somatostatin exert their effects on cell growth, proliferation, differentiation and secretion. Specific actions of each receptor type have been reported, to be implicated in one or more of the cell fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 124 publications
1
9
1
3
Order By: Relevance
“…In this respect, elevation of intracellular Ca 2+ through membrane androgen receptors, in a specific time-dependent form, may prevent activation of catecholamine release by other cellular mechanisms. It is of note that similar results have been obtained in adrenomedullary cells following exposure to opioids which also increase intracellular Ca 2+ levels (reviewed in [65]), and as a result inhibit catecholamine secretion [66][67][68].…”
Section: Discussionsupporting
confidence: 60%
“…In this respect, elevation of intracellular Ca 2+ through membrane androgen receptors, in a specific time-dependent form, may prevent activation of catecholamine release by other cellular mechanisms. It is of note that similar results have been obtained in adrenomedullary cells following exposure to opioids which also increase intracellular Ca 2+ levels (reviewed in [65]), and as a result inhibit catecholamine secretion [66][67][68].…”
Section: Discussionsupporting
confidence: 60%
“…Special attention should be paid to the opioid sequence f114-119. Data from the literature have indeed shown that opioid peptides including α-casomorphins are able to interact with somatostatin receptors [46,47], which are also present on intestinal epithelial cells as well as on the parental HT29 cells. Somatostatin, synthesized and secreted by endocrine D cells of the stomach and intestine, is known to exert an inhibitory control in the gut.…”
Section: Discussionmentioning
confidence: 97%
“…Since J-2156 does not bind per se mu-opiod receptors (Ki 410 μM) this effect can only be explained by an intracellular signaling pathway. Potential interactions of SST receptors with opioid receptors have been suggested (Betoin et al, 1994;Hatzoglou et al, 2005;Maurer et al, 1982;Pfeiffer et al, 2002;Prinster et al, 2005). A recent study showed, that SSTR4 and delta-opioid receptors exist in a heteromeric complex in the spinal cord and function in synergistic manner (Somvanshi and Kumar, 2014).…”
Section: J-2156 Reduces Excitability Of Spinal Nociceptive-specific Nmentioning
confidence: 95%